IMPLEMENTATION OF PROJECT-BASED LEARNING (PjBL) MODEL IN IMPROVING CRITICAL THINKING SKILLS AND ABILITY TO COOPERATE IN PANCASILA EDUCATION CONTENT OF GRADE IV IN ELEMENTARY SCHOOL - Sari, Raihanah; Mutiani, Mutiani; Abbas, Ersis Warmansyah; Subiyakto, Bambang; Handayani, Mutia (International Conference On Social Science Education, 2024)
The investigation conducted points to empowering students to address issues concerning basic learning abilities and the ability to work together within the Pancasila Instruction content in primary schools. One of the arrangements for this issue is to utilize the Project-Based Learning (PjBL) model, which is integrated into the teaching and learning process. This research employs a quantitative approach and a qualitative approach in classroom activity research (CAR) exercises. The inquiry results showed that fundamental considering abilities, which received an evaluation of 90% with the criteria of "exceptionally gifted," and the capacity to work together received an appraisal of 87% with the criteria of "exceptionally competent." Based on the information and results of the investigation obtained, it can be concluded that the use of the Project-Based Learning (PjBL) model can strengthen fundamental critical thinking abilities and the capacity to work together, providing a significant and positive impact on student learning results.